Minarets of Baghdad: Monuments of Architectural Identity - Hassan Mahmood Haj Kasim (Iraqi Journal of Architecture and Planning, 2018)
Minarets are distinctive architectural elements which defines the architectural identity of the Islamic cities both old and new through its vertical appearance ... The sky line of Baghdad -as one of the oldest Islamic capitals – is distinguished by set of minarets dating back to different eras ... These minarets seem as important elements that determine the place identity of Baghdad in drawings and photographs of foreign travelers ... The heritage minarets of Baghdad had architectural features that distinguish it from other minarets of other Islamic cities, despite the succession of periods and foreign influences .In the modern era, many minarets in Baghdad was built carrying strange architectural forms and characteristics from the distinctive identity of traditional minarets of Baghdad, may be due to the lack of knowledge in determining the distinguishing architectural characteristics of that heritage minarets...This paper aims to diagnose the architectural characteristics of the heritageminarets of Baghdad, which the paper suppose that these characteristics are distinctdespite succession of periods and are important elements in defining the distinctiveidentity of Baghdad sky line, in order to provide database for architectural designers,to employ that knowledge in their future designs.Keywords: Architecture of Baghdad, minarets, architectural identity